Parenting Policies and Culture in Academia and Beyond: Making It While Mothering (and Fathering) in the Academy, and What COVID-19 Has to Do with It - Willey, Nicole L. (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
For those of us involved in MIRCI, it is no surprise that being a mother in academia is often seen as a liability. In fact, Anna Young found that “no other industry has a higher ‘leak’ rate for mothers” than academia, and she surmises this is partly because “the upper echelons of the academy are still overwhelmingly dominated by men”—a cultural institution that historically has been “a place by and for men” (x). Recently, the COVID-19 pandemic has exacerbated these inequities in our workplaces. As a matter of maternal health and reproductive freedom, academic mothers must be considered in policies in academia. This article will examine necessary policy and culture shifts that can help mothers in the academy while also discussing personal and local decisions that can be made by those with institutional power that can immediately improve the conditions of mothers in the academy. Of course, we should continue to push for larger systemic changes—such as fair parental leave policies and quality as well as affordable universal child care that need to happen at a societal level—but until those developments are a given, we should work on the following steps, which will be expanded below: 1) Individual choices to not bifurcate our lives into parenting and scholarship; 2) reappointment, tenure, and promotion (RTP) decisions recognizing the importance of interdisciplinary and autoethnographical scholarship, along with enforcing policies and transparency around tolling or stopping the tenure clock and fair research productivity expectations; 3) tolling policies to account for the time needed for the parenting of young children, with options for being part-time on the tenure track or remote teaching possibilities; 4) local decisions to provide intentional community and friendship to parents as well as dedicated space for breastfeeding mothers and children on campus; and 5) sensible scheduling. Our ultimate goal must be larger systemic changes towards parental leave and childcare that will grant the types of policies that will help all parents. In the meantime, we need to use everything we have to help our colleagues who are raising the next generation.